A Comparative Study of IT Outsourcing Management in Australia and Taiwan - Lin, Chad; Lin, K.; Huang, Y.; Liu, Y. (Journal of International Management Studies, 2007)
Growth in IT outsourcing is expected to remain high in the coming years as there have been widespread market claims that IT outsourcing can reduce firms' costs by over 30 percent. The scope and range of IT outsourcing services are also increasing, as evidenced by the promotion of ASP (applications service providers), global outsourcing, software development outsourcing, and web and e-business outsourcing. However, management of IT outsourcing evaluation is particularly under-studied, especially in how these firms measure their IT outsourcing contracts and ensure that benefits expected from these contracts are delivered. The main objective of this paper is to examine and compare the current management practices in IT outsourcing evaluation and benefits realization by Australian and Taiwanese firms. The paper first reviews relevant literature with respect to IT outsourcing, the evaluation of IT outsourcing, and IT benefits realization. Key survey findings from the Australian and Taiwanese firms will be presented.